Training and development experience for agriculture people: Uzel Academy Sample - Kaklıkkaya, Mustafa (My University, 2010)
21. yy.da firmalar, küreselleşme ve teknolojik gelişmeler sonucunda birçok değişim ve gelişimle karşı karşıya kalırlar. Bu yüzden, var olabilmek ve gelişebilmek için rekabet güçlerini arttırmak zorundadırlar. Rekabette başarılı olabilmek için, iyi eğitilmiş ve işletmelere iyi adapte olmuş personele ihtiyaç vardır. Bunların yanı sıra, personelin eğitim ve gelişimi sürekli olmalıdır. Teknolojik ilerlemeler ve küreselleşme tarım sektöründeki firmalarda da değişimlere sebep olmaktadır ve bu değişimlerle başa çıkabilmek için çalışanların sürekli eğitilmesi gerekmektedir. Gelişim, Tarım Sektörü, Personelin Etkinliği, Müşteri Memnuniyeti ve Karlılık.

In the 21st Century, companies face with fast and important changes and improvements that happen because of globalization and customer demands. Therefore, they have to raise their competition power in order to exist and develop their employees. To be accomplished in wild competition, companies need staff who should be well trained and well adopted to their companies. Moreover, training and development process must gain continuity. Globalization and Technological shifts lead to changes even in agriculture organizations. In order to cope with these rapid changes, agriculture companies need to train and develop their employees. Key Words: Training and Development, Agriculture Sector, Employee Efficiency, Customer Satisfaction and Profit.
Keywords: Eğitim ve Gelişim; İnsan Kaynakları Yönetimi; Karlılık; Müşteri Memnuniyeti; Tarım